Morphometric and Length–Weight Relationship of Sea Cucumbers (Holothuriidae) in Northern Waters of Tunda Island, Banten - Syarlla Putri Ara Fitria; Hafiz Hanania Rosadi; Firda Adzkiya Nur Fatahillah; Qien Ratu Syafa'ah; Shofi Nur Alamsyah; Prakas Santoso (Universitas Islam Lamongan, 2026)
Sea cucumbers (family Holothuriidae) are economically important marine invertebrates that are increasingly exploited, raising concerns about the sustainability of their populations. Sea cucumbers are economically valuable and contain bioactive compounds, making them important fisheries resources. This study aimed to analyze the morphometrics and length–weight relationship of sea cucumbers in the northern waters of Tunda Island, Banten. Sampling was conducted on 20–21 September 2025 using hand picking within 50 × 50 cm transects, with a total of 18 individuals collected. Morphometric parameters, including body length, diameter, and Body Basal Area (BBA), were measured under in situ and ex situ conditions. Linear regression analyses were performed to determine the relationships between these parameters and body weight. Results showed that BBA was the most reliable predictor of body weight, with R² = 0.731 for ex situ measurements, while in situ measurements had higher variability (R² = 0.219). Diameter and length had lower predictive power. These findings provide baseline data for sustainable management and utilization of sea cucumber populations. Future studies should integrate physiological variables, seasonal variation, and image-based morphometrics to enhance biomass estimation and conservation strategies.